2019
DOI: 10.3390/risks7010016
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Options and Computing Implied Volatilities using Neural Networks

Abstract: This paper proposes a data-driven approach, by means of an Artificial Neural Network (ANN), to value financial options and to calculate implied volatilities with the aim of accelerating the corresponding numerical methods. With ANNs being universal function approximators, this method trains an optimized ANN on a data set generated by a sophisticated financial model, and runs the trained ANN as an agent of the original solver in a fast and efficient way. We test this approach on three different types of solvers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 26 publications
1
63
0
Order By: Relevance
“…For example, in order to approximate the Black-Scholes implied volatilities based on the Heston input parameters, two numerical methods are required, i.e., the COS method to calculate the Heston option prices and Brent's root-finding algorithm to determine the corresponding implied volatility, as presented in Figure 1. Using two separate ANNs to map the Heston parameters to implied volatility has been applied in Liu et al (2019). In the present paper, we merge these two ANNs, see Figure 1.…”
Section: The Forward Pass: Learning the Solution With Annsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in order to approximate the Black-Scholes implied volatilities based on the Heston input parameters, two numerical methods are required, i.e., the COS method to calculate the Heston option prices and Brent's root-finding algorithm to determine the corresponding implied volatility, as presented in Figure 1. Using two separate ANNs to map the Heston parameters to implied volatility has been applied in Liu et al (2019). In the present paper, we merge these two ANNs, see Figure 1.…”
Section: The Forward Pass: Learning the Solution With Annsmentioning
confidence: 99%
“…The global structure is depicted in Figure 6. More details on the ANN solver can be founded in (Liu et al, 2019). As a data-driven method, the samples from the parameter set for which the ANN is trained are randomly generated for the pricing of European put options.…”
Section: The Forward Passmentioning
confidence: 99%
“…Concerning the second problem, the inverse of the call function does not have an analytical representation and therefore the problem can only be approached by numerical methods (Newton-Raphson and other iterative schemes) and, in some instances, even those methods may fail for technical reasons (Orlando and Taglialatela 2017;Dura and Moşneagu 2010;Lorig et al 2014;Liu et al 2019). Recently, Liu et al (2019) and Cao et al (2019) suggested new numerical methods to reconstruct the volatility through neural networks.…”
Section: N (X)mentioning
confidence: 99%
“…MLP able to solve non-linear problems while maintaining the original structure of perceptron of feedforward layered [25]. Neural network has been demonstrated to successfully employed in various field of studies such as medical [26], [27], agriculture [28], [29], industrial [30], [31] and finance [32], [33].…”
Section: A Neural Networkmentioning
confidence: 99%